Optimizing Digital Learning Based Learning as a Learning Media of Today with Enhanced Microsoft Office Softskill at SMAS Husni Thamrin - Herawati, Elvina; Mahyuddin; Sutarman; Sawaluddin; Erwin; Marpaung, Jonathan Liviera (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Education has had a substantial metamorphosis in the current age of computers and the Internet. The adoption of digital learning technology represents a significant paradigm shift. Schools should optimize the utilization of this technology to enhance learning results. The field of education is seeing significant transformations in the current era of information and technology. Global educational institutions are increasingly using digital-centric learning methods to stay abreast with contemporary advancements. Enhancing the efficiency of technology-driven education in educational institutions is a crucial measure in equipping upcoming generations for the future. The primary advantage of digital learning is its inherent flexibility, since it enables students to access educational resources at their convenience and from any location. This allows them to tailor their learning experience to their individual pace and preferred methods of learning. It aids in surmounting the temporal and spatial limitations associated with traditional education. Furthermore, digital learning facilitates the utilization of a diverse range of educational resources. Students can enhance their comprehension of ideas by utilizing simulations, films, and other interactive materials. The Mathematics Teachers Team at USU organized a Microsoft Excel training session at Husni Thamrin SMAS with the objective of enhancing the teaching and learning paradigm for teachers in schools.